Public Relations of Prabowo Subianto's Political Relations for Gen Z Voters in the 2024 Presidential Election - Gauri, Anna Purnama (Institute of Computer Science (IOCS), 2024)
Along with the development of information technology, currently the media is entering a new phase called new media, namely internet-based mass media that can be accessed online. Mass media is a means of publication, as well as a means of building reputation. The aim of this research is to analyze the role of Prabowo Subianto's political public relations for Gen Z voters in the 2024 presidential election. This research method uses descriptive qualitative methods with textual analysis of news related to the role of Prabowo's PPP for Gen Z voters. The results of this research show that the formation of a political image This new one is used to present Prabowo as a civil politician and position himself close to the community. This method is also used to attract the attention of young voters who will be the deciding group in the 2024 election.